Technology exploration of zero-emission regional aircraft: why, what, when and how? - Pontika, Evangelia; Laskaridis, Panagiotis; Ansell, Phillip J.; Haran, Kiruba; Navaratne, Rukshan; Kipouros, Timoleon (Elsevier, 2026)
The paper focuses on the exploration and comparison of zero-emission technology strategies for regional aircraft. While significant progress is made on the development of technologies, systems and aircraft configurations, major challenges and uncertainties mean that various strategies are considered but are difficult to compare as they rely on different technologies, metrics, requirements, maturity levels and sustainability targets. A novel, holistic approach that captures inter-dependencies, synergies and combined impact of technologies is developed to evaluate the feasibility of such aircraft over 2 horizons, quantify performance and emissions through various phases of the life cycle, establish technology bottlenecks and required step changes and classify developments in terms of impact and risk. For at least 30 passengers at 300 nmi, significant advances are required for fuel cells (2 kW/kg), electric machines (13 kW/kg), power distribution ( > 1.5 kVolts), and thermal management systems (3.5 kW/kg and 3.5 kW/kW). These will lead to major mission level ( + 90%) and lifecycle energy penalties (up to + 177%) with a carbon intensity level of 6.5 kgCO2/kgH2 (ex. blue, turquoise, green hydrogen) required to breakeven current CO2 levels. Step changes including superconductivity and high temperature fuel cells, along with aircraft mass and drag reductions are required to increase capacity to pax > 40 and 800 nmi, and achieve energy reductions against existing designs. The energy density of batteries and the need of gas turbines to meet diversion and hold requirements limit full electric variants to 30 passengers at 200 nmi with 480 Wh/kg battery energy density but they can offer an exceptional energy per passenger benefit ( ∼ 40% reduction) against current aircraft.
Keywords: 40 Engineering; 7 Affordable and Clean Energy; 13 Climate Action; Aerospace & Aeronautics; 4001 Aerospace engineering; Fuel cells; Batteries; Hydrogen; Aviation; Roadmaps